Students’ Critical Thinking Skills in Solving PISA-Like Questions in the Context of the Jakabaring Palembang Tourism - Marta Risa Putri Utami; Zulkardi Zulkardi; Ratu Ilma Indra Putri (Universitas Sriwijaya, 2023)
The essence of the independent curriculum and Pancasila student profile requires teachers to adapt teaching materials to the PISA framework and invite students to think critically. For this reason, this qualitative descriptive research aimed to describe students' critical thinking skills in solving mathematical PISA-like questions on the quantity content in the context of the Jakabaring Palembang tourism using the Indonesian Realistic Mathematics Education (PMRI in Bahasa) approach. This research involved 36 under-15 students of a junior high school in Palembang. Data from observations, tests, and interviews were collected and analyzed qualitatively to measure students' critical thinking skills. The results of this study indicated that the students' critical thinking ability belonged to the moderate category, with a total of 22 students in this category. The highest scoring critical thinking indicator was interpretation (86.1%), while the lowest was analysis (13.8%). The former was dominant in students because when learning using the PMRI approach, students could model problems into their interpretations. Solving PISA-like questions could train students to develop the interpretation indicator of critical thinking skills and at the same time introduce the Palembang Jakabaring tourism.